ANALISIS STRUKTUR VEGETASI HUTAN MANGROVE DI KAWASAN REKLAMASI PULAU SERANGAN, KOTA DENPASAR - I Ketut Sundra (Environmental Research Center (PPLH) of Udayana University)
This research was conducted in Serangan island in August, 2004. Ten plots assampling units were taken using Systematic Plot Design. Two parameters : ImportanceValue and Diversity Indices were determined on vegetation analyses. Samples were takenfrom three different locations. Soil analysis was conducted for determining macro elementscontent, such as: N, P, K and others organic maters.The result shows that there are 13 species of mangrove found. Five species areclassified into ‘pure’ mangrove and others are associate. Rhizophora apiculata (withImportant Value, IV, of 103.252 %) and Sonneratia alba (IV 99.663 %) are two species thathave high importance value (IV). In addition, the diversity of mangrove in Serangan islandis found to be low (diversity indices 0.791).Results of this study indicate that after reclamation, the mangrove ecosystem inSerangan is in unstable conditions.